Dual-color control of nucleotide polymerization sensed by a fluorescence actuator - Reimao-Pinto, Madalena M.; Ana Cordeiro; Carina Almeida; Pinheiro, Andre V.; Artur Moro; Lima, Joao C.; Pedro V. Baptista (Photochemical & Photobiological Sciences, 2014)
n/a
Moro, Artur/C-6689-2013; Lima, Joao/F-3658-2010; Baptista, Pedro/A-1237-2009; Lima, Joao Carlos/K-2890-2014 Moro, Artur/0000-0003-3285-4919; Lima, Joao/0000-0003-0528-1967; Baptista, Pedro/0000-0001-5255-7095; 0